Спектральный и временной анализ пульсограмм - Яцышин, В. И.; Письменецкий, В. А.; Головенко, В. М. (ХТУРЭ, 1998)
Dispersion Fourier proceccor operation is applied for noninvasive tests of dynamic flow of blood. The device for measnring and analysis of pulsewave at human finger.Registration of pulsewave is realised on foto-to-optic convertor. Analog signal is filtered, converted to digital fnd connected with PC. The program allows analysis of pulsewave parameters, reflection of measuring results and drawing of pulsewave characteristics.
Keywords: анализ спектральный; пульсограмма